PENGARUH LINGKUNGAN KERJA FISIK DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR SATUAN PELAYANAN TTA DARA KOTA BIMA - Syarif Hidayatullah; Jaenab - Jaenab (Jurnal Ilmiah Satyagraha, 2021)
The purpose of this study was to determine and analyze the significant effect of physical work environment and workload on employee performance at the TTA Dara service unit, Bima City. The type of research used is associative, with a sample size of 31 respondents. The sampling technique used was saturated sampling. Data collection was carried out by distributing questionnaires using Likert scale measurement. Methods of data analysis using validity test, reliability test, classical assumption test, multiple linear regression analysis, correlation analysis, coefficient of determination, significance test, and simultaneous test. The results of the study can be concluded that the Physical Work Environment has a significant influence on Employee Performance and Workload does not have a significant effect on Employee Performance at the TTA Dara Service Unit Office in Bima City, where the t value of the Physical Work Environment variable is 2,188 greater than the t table value. amounting to 2,051 (2,188 2,051) with a significance value of 0.043 0.05 and the Workload variable of -1,126 is smaller than 2,051 (-1,126 2,051) with a significance value of 0.270 0.05. Work environment and workload have a significant effect on employee performance at the TTA Dara service unit office in Bima City